Neuroaxonal Dystrophy in a Flock of Pied Imperial Pigeons (Ducula bicolor). Issue 4 (May 2017) - Barrows, M.; Killick, R.; Day, C.; Saunders, R.; Baiker, K.; Ressel, L.; Denk, D.
Summary: Five juvenile pied imperial pigeons ( Ducula bicolor ) presented with neurological signs including torticollis, ataxia and poor flying ability. All were humanely destroyed and submitted for post-mortem examination. Microscopically, the most significant findings were in the brain and spinal cord. Spheroid formation was evident within the medulla, pons, diencephalon, cortical grey and subcortical white matter, spinal cord white and grey matter and the granular and molecular cell layers of the cerebellum. There was no evidence of associated inflammation. Immunohistochemistry revealed positive labelling within the spheroids for S100 axons and phosphorylated neurofilaments including SMI31, neurofilament cocktail and microtubule-associated protein 2. Transmission electron microscopy confirmed the light microscopical findings of frequent axonal spheroids. These results are consistent with neuroaxonal dystrophy, which has not been described previously in pigeons. This highlights the importance of considering neuroaxonal dystrophy in juvenile birds with neurological signs. A genetic basis is suspected in this group.